Dokumenti za Georgi Rakovski v Osmanskite Arhivi - 880-01 Sabev, Orlin, 1970- (Sofiya)
149 sayfa
Keywords: The numerous studies dedicated to the life and revolutionary activity of Georgi Rakovski (1821-1867) are based on extremely rich and diverse archival material - his personal archive, Greek, Serbian, Romanian, Russian and Austrian archives, memoires and letters of his contemporaries, etc. However, an mportant source as the Ottoman archives, with few exceptions, still remains unexplored. For the purposes of the present publication, a systematic and in-depth research of the Ottoman Archive in Istanbul was conducted and 70 relevant archival units were found out. They contain over a hundred documents, predominantly in the Ottoman Turkish and a few in the French language, which are directly or indirectly related to Georgi Rakovski. These documents reveal curious and previously unknown details about his personality and revolutionary activity. In the current research 45 out of a total of over a hundred documents are presented in full Bulgarian translation. In terms of content, the documents are related to the following five topics : a) the imprisonment of Georgi Rakovski and his father Stoyko Popovich in Istanbul in 1845-1848; b) Rakovski’s commercial affairs and financial relationships with other entrepreneurs and creditors; c) his revolutionary activity; d) his associates; e) his journalistic and writing activity.